A molecular phylogeny of marine amphipods in the herbivorous family Ampithoidae. (10th June 2016) - Sotka, Erik E.; Bell, Tina; Hughes, Lauren E.; Lowry, James K.; Poore, Alistair G. B.
Abstract : Ampithoid amphipods dominate invertebrate assemblages associated with shallow‐water macroalgae and seagrasses worldwide and represent the most species‐rich family of herbivorous amphipod known. To generate the first molecular phylogeny of this family, we sequenced 35 species from 10 genera at two mitochondrial genes [the cytochrome c oxidase subunit I (COI) and the large subunit of 16 s (LSU)] and two nuclear loci [sodium–potassium ATPase (NAK) and elongation factor 1‐alpha (EF1)], for a total of 1453 base pairs. All 10 genera are embedded within an apparently monophyletic Ampithoidae ( Amphitholina, Ampithoe, Biancolina, Cymadusa, Exampithoe, Paragrubia, Peramphithoe, Pleonexes, Plumithoe, Pseudoamphithoides and Sunamphitoe ). Biancolina was previously placed within its own superfamily in another suborder. Within the family, single‐locus trees were generally poor at resolving relationships among genera. Combined‐locus trees were better at resolving deeper nodes, but complete resolution will require greater taxon sampling of ampithoids and closely related outgroup species, and more molecular characters. Despite these difficulties, our data generally support the monophyly of Ampithoidae, novel evolutionary relationships among genera, several currently accepted genera that will require revisions via alpha taxonomy and the presence of cryptic species.